The relevance of life-cycle CO₂ emissions for vehicle purchase decisions: A stated choice experiment for Germany - Michaela V. Gerhardt; Elke D. Kanberger; Andreas Ziegler (Philipps-University Marburg, School of Business and Economics, 2023)
This paper examines the individual preferences for a reduction of life-cycle CO2 emissions in vehicle purchase decisions. The empirical analysis is based on data from a stated choice experiment with more than 1,100 citizens in Germany that refers to decisions between three types of electric vehicles and a conventional (i.e. gasoline or diesel) vehicle that are characterized by several attributes like purchase price or fuel costs. With respect to CO2 emissions, we specifically examine emissions in vehicle production besides the commonly considered emissions in vehicle use. Our econometric analysis with flexible mixed logit models reveals a strong stated preference for the reduction of CO2 emissions in both vehicle use and production, whereby the estimated willingness to pay for CO2 emission reductions is higher for vehicle production. Furthermore, we find that conventional vehicles are significantly preferred over plug-in hybrid electric vehicles and particularly strongly significantly preferred over extended-range and pure electric vehicles. Surprisingly, environmental attitudes, i.e. environmental awareness and ecological policy identification, have no significant effects on the reduction of CO2 emissions in both vehicle use and production. These results suggest that citizens in Germany with strong environmental identity do not consider reductions of CO2 emissions in vehicle purchase decisions as an important direction for climate protection. Instead, this group rather tends to avoid the purchase of conventional vehicles since environmental attitudes have a significantly positive effect on the stated choice of electric vehicles, whereby this estimated effect is dominated by an ecological policy orientation instead of general environmental awareness. The latter result suggests the strong relevance of the controversial political discussion about the transition to electromobility in Germany. By considering economic preferences, the econometric analysis additionally reveals that individual trust is relevant for the purchase of plug-in hybrid electric vehicles.
Keywords: 330; Vehicle purchase decisions; CO2 emissions in vehicle use and production; climate protection; electric vehicles; stated choice experiment; mixed logit models